2018
DOI: 10.1021/acs.nanolett.8b00548
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Magnetic Light Emission with All-Dielectric Optical Nanoantennas

Abstract: Electric and magnetic optical fields carry the same amount of energy. Nevertheless, the efficiency with which matter interacts with electric optical fields is commonly accepted to be at least 4 orders of magnitude higher than with magnetic optical fields. Here, we experimentally demonstrate that properly designed photonic nanoantennas can selectively manipulate the magnetic versus electric emission of luminescent nanocrystals. In particular, we show selective enhancement of magnetic emission from trivalent eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 53 publications
3
62
0
Order By: Relevance
“…A similar comparison can be performed between the genetically optimized antenna and other commonly used dielectric resonators for enhanced magnetic fields such as a single silicon disk or a dimer of Si disks (see Figure S5, Supporting Information). Importantly, the magnetic field intensity enhancements simulated here for a disk dimer and a hollow nanodisk are in good agreement with recently reported experimental values, validating the relevance of the comparison made here. These simulations indicate that the GA design offers a very significant enhancement of the magnetic field intensity above the antenna that is 10× and 8× larger than for a single disk or a dimer, respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A similar comparison can be performed between the genetically optimized antenna and other commonly used dielectric resonators for enhanced magnetic fields such as a single silicon disk or a dimer of Si disks (see Figure S5, Supporting Information). Importantly, the magnetic field intensity enhancements simulated here for a disk dimer and a hollow nanodisk are in good agreement with recently reported experimental values, validating the relevance of the comparison made here. These simulations indicate that the GA design offers a very significant enhancement of the magnetic field intensity above the antenna that is 10× and 8× larger than for a single disk or a dimer, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Hollow nanodisks (i.e., nanocylinders) were proposed to overcome this hurdle, granting access to the magnetic field that would be partially enhanced in air and not entirely in the dielectric material. We recently used this approach to experimentally couple such structures to magnetic emitters, demonstrating the manipulation of the magnetic local density of states . However, it is still very challenging to place a nanoscale piece of material inside hollow nanodisks, making nanostructures featuring easily accessible magnetic hotspots particularly appealing.…”
Section: Introductionmentioning
confidence: 99%
“…The contrasts of electric and/or magnetic LDOS close to dielectric nanostructures are in agreement with recently published experimental results, showing a clear separation of electric and magnetic LDOS above the dielectric structures. 24,46 Also the quantitative trends in the intensity ratios are correctly recovered by the simulations, showing an enhancement of the luminescence intensity by a factor of around 3 for the MD transition and 1.5 in the ED case.…”
Section: Discussionmentioning
confidence: 60%
“…21 Lanthanoid ions (also known as rare earth elements) such as europium (Eu 3+ ) exhibit ED and MD transitions of similar strength 22 and can be used as probes of the optical magnetic near field. 23,24 A peculiarity of Eu 3+ is that electric and magnetic dipole transitions of comparable strength occur at close wavelengths. ED and MD transitions of Eu 3+ both start from the 5 D 0 energy level via de-excitation to the 7 F 2 (ED) and the 7 F 1 level (MD).…”
mentioning
confidence: 99%
“…21,29 In particular, we previously demonstrated that by changing the distance between a nanoparticle containing electric and magnetic dipolar transitions and a gold strip of micrometer size, we could engineer their respective electric and magnetic emission, 29 in the same way it was predicted and demonstrated by K. H Drexhage 30 and Chance et al 14 This approach Nevertheless, in order to go further in the engineering of the interactions between magnetic light and matter, it is necessary to design nanostructures allowing to boost these interactions. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Along those lines, we recently demonstrated for the first time how dielectric nanoantennas were able to enhance the magnetic emission of quantum emitters 34 and researchers have demonstrated, through assemble measurements, that metallic nanostructured films could promote the transmission of magnetic emission. 26 But so far, only theoretical works have studied and demonstrated the ability of single plasmonic nanostructures [35][36][37][38] to manipulate the spontaneous emission of MD transitions by manipulating the magnetic LDOS at the nanoscale.…”
mentioning
confidence: 99%